Children and Youth at Risk in Times of Transition : International and Interdisciplinary Perspectives - Borge, Baard Herman 1963- HerausgeberIn; Kleinau, Elke 1954- HerausgeberIn; Ødegaard, Ingvill Constanze HerausgeberIn (Studies in the History of Education and Culture / Studien zur Bildungs- und Kulturgeschichte, 2024)
Children and youth belong to one of the most vulnerable groups in societies. This was the case even before the current humanitarian crises around the world which led millions of people and families to flee from wars, terror, poverty and exploitation. Minors have been denied human rights such as access to education, food and health services. They have been kidnapped, sold, manipulated, mutilated, killed, and injured. This has been and continues to be the case in both developed and developing countries, and it does not look as if the situation will improve in the near future. Rather, current geopolitical developments, political and economic uncertainties and instabilities seem to be increasing the vulnerability of minors, especially in the wars and armed conflicts currently being waged not only in Europe, but on almost every continent. How can risks children and youth are exposed to in times of transition be reduced? Which role do state agencies, non-governmental organisations, as well as children’s coping strategies play in mitigating the vulnerabilities of minors? This volume addresses risks to which children and young people are exposed, especially in times of transition. The focus is on different groups of children in the European wartime and post-war societies of the Second World War, ‘occupation children’ in Germany, teenage National Socialist collaborators in Norway, and more recent cases such as child soldiers, refugee children, and children of European “Islamic State” fighters. The contributions come from international scholars and different academic disciplines (educational and social sciences, humanities, law, and international peace and conflict studies) and are based on historical, quantitative, and/or qualitative analyses. ; Children and youth belong to one of the most vulnerable groups in societies. This was the case even before the current humanitarian crises around the world which led millions of people and families to flee from wars, terror, poverty and exploitation. Minors have been denied human rights such as access to education, food and health services. They have been kidnapped, sold, manipulated, mutilated, killed, and injured. This has been and continues to be the case in both developed and developing countries, and it does not look as if the situation will improve in the near future. Rather, current geopolitical developments, political and economic uncertainties and instabilities seem to be increasing the vulnerability of minors, especially in the wars and armed conflicts currently being waged not only in Europe, but on almost every continent. How can risks children and youth are exposed to in times of transition be reduced? Which role do state agencies, non-governmental organisations, as well as children’s coping strategies play in mitigating the vulnerabilities of minors? This volume addresses risks to which children and young people are exposed, especially in times of transition. The focus is on different groups of children in the European wartime and post-war societies of the Second World War, ‘occupation children’ in Germany, teenage National Socialist collaborators in Norway, and more recent cases such as child soldiers, refugee children, and children of European “Islamic State” fighters. The contributions come from international scholars and different academic disciplines (educational and social sciences, humanities, law, and international peace and conflict studies) and are based on historical, quantitative, and/or qualitative analyses